2012
DOI: 10.1002/elan.201200487
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Antimony(III) and Molybdenum(VI) by Adsorptive Stripping Voltammetry Using Quercetin as Complexing Agent

Abstract: A sensitive and selective voltammetric method for simultaneous determination of Sb(III) and Mo(VI) using Quercetin (Q) as complexing agent is described. Optimal conditions were found to be: pH 3.7, CQ=6.0 µmol L−1 and Eacc=−0.10 V. The LOD (3σ) for Sb(III) are 0.076 and 0.040 µg L−1, whereas for Mo(VI) are 0.086 and 0.048 µg L−1 with tacc of 60 and 120 s, respectively. The method was validated using synthetic sea water (ASTM D665) and was applied to the determination of Sb(III) and Mo(VI) in natural waters wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
11
1
1
Order By: Relevance
“…These are summarized in Table 3. As can be seen from this table, the value of LOD is lower than most of the reported electrochemical methods [15,16,[21][22][23]26,[31][32][33]36,[38][39][40]43,45,49,52]. Moreover, the results of the interference studies showed that the selectivity of the proposed method is quite high.…”
Section: Comparison Of Proposed Methods With Other Methodscontrasting
confidence: 40%
See 3 more Smart Citations
“…These are summarized in Table 3. As can be seen from this table, the value of LOD is lower than most of the reported electrochemical methods [15,16,[21][22][23]26,[31][32][33]36,[38][39][40]43,45,49,52]. Moreover, the results of the interference studies showed that the selectivity of the proposed method is quite high.…”
Section: Comparison Of Proposed Methods With Other Methodscontrasting
confidence: 40%
“…Many voltammetric studies, including stripping methods for determination of antimony, have focused on the modification of the electrode surface or use of a chelating/complexing agent to increase the detection limit. With this aim, different complexing reagents such as catechol [33,44], chloranilic acid [34,36], morin [35], gallocyanine [37], pyrogallol red [38], pyrogallol [39,41,42], alizarin red S [40], 4-(2-thiazolylazo)-resorcinol [43], quercetin [45], and quercetin-5 -sulfonic acid [46] have been successfully used for determination of Sb(III) on a mercurybased electrode. Recently, carbon-based electrodes have attracted attention in electroanalytical studies as an attractive alternative to mercury electrodes in stripping analysis due to their many advantages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A preocupação com este compartimento ambiental é significativa, devido aos possíveis riscos aos quais organismos aquáticos estão expostos. 33,34,[37][38][39][40][41][42][43] No mesmo sentido, alguns trabalhos também avaliaram a presença de metais em águas de torneira e água envasada. [44][45][46][47][48][49] Arab and Alshikh avaliaram a presença de Cd, Cu, Fe, Pb Zn, Se em amostras de águas de torneira de diferentes pontos da cidade de Jeddah na Arábia Saudita, durante um ano empregando voltametria de redissolução por pulso diferencial e HMDE como eletrodo de trabalho.…”
Section: Determinação De íOns Metálicos Usando O Hmdeunclassified